PENERAPAN MODEL PROBLEM BASED LEARNING DENGAN PENDEKATAN TARL UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS VII G DI SMP NEGERI 9 PALU - Eka Widhiani, Ni Luh Regita; Sukayasa, Sukayasa; Nubaya, Siti (LPPM Universitas Bina Bangsa, 2024)
This research was conducted with the aim of improving the learning outcomes of class VII G students at SMP Negeri 9 Palu in the Mathematics subject, Addition and Subtraction of Whole Numbers, through the application of the Problem Based Learning (PBL) learning model with the Teaching at The Right Level (TaRL) approach. This type of research is Classroom Action Research (PTK), the subjects of this research are students in class VII G of SMP Negeri 9 Palu, consisting of 33 students. The data collection instrument used in this research was a multiple choice test which was carried out at the end of the meeting. The data analysis used is quantitative descriptive. As a result of the first cycle of research, students obtained an average science learning outcome score of 57.27 and a student completeness level of 84.85%. This has increased from the previous pre-cycle results. Furthermore, in cycle II the average value of students' Mathematics learning outcomes increased to 61.30 with a student completeness level of 81.82%. It can be concluded that improving the learning outcomes of class VII G students using the Problem Based Learning (PBL) learning model with the TaRL approach can improve students' Mathematics learning outcomes.